Critical Synthesis Package: Structured Communication Adolescent Guide (SCAG) - Godwin Dogbey (Association of American Medical Colleges, 2014)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the basic descriptive and psychometric properties of the Structured Communication Adolescent Guide (SCAG), and (2) a copy of the SCAG with the scoring instructions and picture documentation of the use of instrument developed by Kim Blake, MD. The SCAG is a 30-item checklist designed to help medical students receive feedback about their interviewing skills with adolescents. The measure consists of four domains labeled: Getting Started, Gathering Information, Teen Alone-Including Lifestyles, and Wrap Up. The items are rated on a 3-point Likert-type scale (0 = Did Not, 2 = Did Well). The items are simple statements that the rater, an adolescent patient, uses to assess the provider. A brief explanation of the instructions on scoring is provided at the upper part of the guide. An additional column is provided for general comments from the rater regarding favorable (positive) and unfavorable (negative) things that stood out during the interview. The general rating is based on a 5-letter scale (A = Excellent, F = Fail). For scoring purposes, numerical values can be assigned to these alphabetic anchors. French, Spanish, and German language versions of the SCAG exist in the same format as the English language version. A picture guide that gives visual context to how the guide is used in practical face-to-face situations constitutes part of the complete repertoire of the supplemental materials. Studies reported that SCAG has been found to be both reliable and valid. Although the SCAG was translated into other languages, studies that used them in those languages were not readily available or accessible. The adaptation of the SCAG for use with other patient populations such as geriatric patients has been suggested, although it was specifically developed for use with adolescents. For medical education purposes, the SCAG can be used over the entire continuum of medical education spanning undergraduate, graduate, and practicing physicians undergoing continuing education, despite its initial development for undergraduate medical education. NOTE: The instrument to which this submission refers is also published within MedEdPORTAL and is available at: www.mededportal.org/publication/798